The Rise and Progress of Western Civilization: What about Islamic Civilization - Gugun Gumelar; Hilmi Aripin; Imam Tabroni; Amina Intes; Ling Barra (Yayasan Adra Karima Hubbi, 2023)
Background. Since the 15th century AD, the course of human civilization has been clear, with Western civilization surpassing its Islamic counterpart. Even today, the strides made by Western civilization continue to be icons of global progress. Purpose. The roots of this civilization can be traced back to Europe, where over the course of six centuries, a series of transformative events took place, including the Renaissance, Industrial Revolution, Aufklarung, and French Revolution. Method. Muslims achieved significant progress during their classical period after a centuries-long process. Therefore, it is not surprising that Europe has achieved great progress in politics, culture and technological advancement, as it has had access to this knowledge for a long period of time. Results. When comparing Western and Islamic civilizations, it is important to note that Islamic civilization reached great heights during its classical period. Conclusion. In the classical era, Western civilization teetered on the brink of darkness, plunging many Europeans into an identity crisis. Meanwhile, Islamic civilization flourished, and Europeans eagerly drew knowledge from its teachings. The 14th to 15th centuries ushered in a period of progress and growth for Western civilization, which influenced other cultures as well. Today, after more than five centuries, Western civilization maintains its dominant position not only over Islamic and Eastern civilizations, but also other civilizations. The 14th to 15th century Renaissance.